Extracorporeal Membrane Oxygenation Versus Off-pump Technique in Lung Transplantation: A Meta-analysis With Reconstructed Time-to-event Data - Passos, Felipe S.; Carvalho E Silva, Maria Clara; Rodrigues, Fabiano Taranto de O.; Oliveira, Rachid Eduardo Noleto da Nobrega; Pessoa, Bernardo M.; Treml, Ricardo E.; Heim, Christian; Siemeni, Thierry; Kirov, Hristo; Doenst, Torsten; Caldonazo, Tulio (Transplantation, 2026)
BACKGROUND: Extracorporeal membrane oxygenation (ECMO) is an important intraoperative support strategy in lung transplantation, particularly for high-risk patients. Although ECMO offers theoretical advantages such as controlled reperfusion and hemodynamic stabilization, its impact on postoperative outcomes compared with off-pump techniques remains debated. This study aimed to evaluate evidence comparing ECMO and off-pump approaches. METHODS: Three databases were assessed. The primary outcome was overall survival. Secondary outcomes included time until extubation, intensive care unit and hospital length of stay (LOS), primary graft dysfunction at postoperative day 3, and need for renal replacement therapy. Hazard ratio, odds ratio, and mean difference (MD) with 95% confidence interval (CI) were calculated. Time-to-event data reconstruction and sensitivity analyses were performed. A subgroup analysis compared planned versus unplanned ECMO to address treatment allocation bias. RESULTS: Six retrospective studies with 1008 patients were included. ECMO was associated with lower overall survival (hazard ratio, 1.555; 95% CI, 1.13-2.15; P = 0.007). ECMO also resulted in longer time until extubation (MD, 1.24 d; 95% CI, 0.38-2.09; P = 0.005), intensive care unit LOS (MD, 2.40 d; 95% CI, 1.20-3.61; P < 0.001), hospital LOS (MD, 3.61 d; 95% CI, 0.81-6.40; P = 0.011), and higher primary graft dysfunction incidence at day 3 (odds ratio, 2.18; 95% CI, 1.34-3.53; P = 0.002). No significant difference was observed for renal replacement therapy ( P = 0.054). Landmark analysis showed poorer survival for patients supported with ECMO during the first 6 mo but not beyond. CONCLUSIONS: ECMO is associated with poorer early survival and adverse outcomes but remains crucial for high-risk patients, underscoring the need for optimized selection and standardized management.
CRIS-Team Scopus Importer:2026-02-06